(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This article explores the cultural and contextual challenges encountered in the translation of subject-specific terminology, with a focus on English-to-Uzbek translation. Translators often face difficulties due to semantic mismatches, differences in realia, connotative meanings, and pragmatic nuances. Drawing on examples from fields such as law, medicine, technology, and linguistics, the paper identifies the nature of these problems and discusses effective solutions. Based on translation theories, the study suggests alternative approaches, including descriptive and functional translation methods and cultural adaptation strategies.